2022
DOI: 10.1039/d2ma00301e
|View full text |Cite
|
Sign up to set email alerts
|

Amine-functionalized stable Nb2CTx MXene toward room temperature ultrasensitive NO2 gas sensor

Abstract: Large surface area and abundant surface functional groups favor the MXene (Nb2CTx) for potential gas sensor applications. However, atmospheric instability is the major limitation of the MXenes. In this work,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…51,91,93–95 Naveen Kumar et al found that covalently modifying MXenes (Nb 2 CT x ) with (3-aminopropyl)triethoxysilane (APTES) via silylation molecules increased the stability and allowed for the simultaneous inclusion of extra reactive NH 2 group. 65 The APTES reduces the MXene oxidation by producing a homogenous, thick protective layer over the surface of Nb 2 CT x . APTES served as an electron acceptor, facilitating electron transfer to NO 2 molecules via MXenes.…”
Section: Recent Advancements In No2 Gas Sensors Using Mxene-based Mat...mentioning
confidence: 99%
See 1 more Smart Citation
“…51,91,93–95 Naveen Kumar et al found that covalently modifying MXenes (Nb 2 CT x ) with (3-aminopropyl)triethoxysilane (APTES) via silylation molecules increased the stability and allowed for the simultaneous inclusion of extra reactive NH 2 group. 65 The APTES reduces the MXene oxidation by producing a homogenous, thick protective layer over the surface of Nb 2 CT x . APTES served as an electron acceptor, facilitating electron transfer to NO 2 molecules via MXenes.…”
Section: Recent Advancements In No2 Gas Sensors Using Mxene-based Mat...mentioning
confidence: 99%
“…example, Naveen Kumar et al demonstrated that the introduction of amine groups over the Nb 2 CT x MXene helps in the detection of acidic gases such as NO 2 by acting as an electron acceptor 65. Rathi et al also modied Nb 2 CT x MXene with CTAB and here the stability enhancement was ascribed to the (i) noncovalent bonding between CTAB and Nb 2 CT x MXene (ii) the long hydrophobic chains in CTAB hinders the interaction of humidity and oxygen with Nb 2 CT x MXene.…”
mentioning
confidence: 99%
“…MXenes can be easily synthesized from their parent bulk MAX phase (A being Al, Si or Ge) by selective etching of A element [3][4][5]. MXenes are highly useful for the detection of toxic gases due to fascinating properties like high surface-to-volume ratio resulting into abundance of gas adsorption sites, metallic conductivity, high signal-to-noise ratio, rich elemental composition and surface terminal groups, mechanical strength and flexibility, and strong hydrophobicity [6,7]. Among MXenes, Ti3C2Tx has been widely explored for gas sensing applications due to its conductive nature [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…28% toward 10 ppm of CO 2 with a mean standard error of 1.9% over 15 days, indicating a decent long-term stability (Figure f). The nice operation robustness probably lay in the presence of the hydrophobic methoxy group within APTES that effectively passivated the reactive sites via direct covering and blocked the external water adsorption within the BP nanosheets . Due to the strong electron-donating property of amine moieties within APTES and p -type property of BP nanosheet, , electrons were spontaneously extracted from APTES to BP, leading to the increase of baseline resistance.…”
mentioning
confidence: 99%
“…The nice operation robustness probably lay in the presence of the hydrophobic methoxy group within APTES that effectively passivated the reactive sites via direct covering and blocked the external water adsorption within the BP nanosheets. 19 Due to the strong electron-donating property of amine moieties within APTES and p-type property of BP nanosheet, 20,21 electrons were spontaneously extracted from APTES to BP, leading to the increase of baseline resistance. Note that the direct interplay between BP and analyte gas was scarce as BP was largely covered by viscous APTES.…”
mentioning
confidence: 99%